Differences between poison and venom: An attempt at an integrative biological approach. (15th February 2021) - Jared, Carlos; Luiz Mailho‐Fontana, Pedro; Maria Antoniazzi, Marta
Abstract: We discuss the use of the terms venom and poison, in the context of integrative biology, with particular emphasis on behaviour and natural history. Our purpose is to reach a broad scientific audience, especially that dedicated to zoology. The meaning of the two terms is reviewed from the secretory perspective, mainly focussed on the reptiles and amphibians. We justify the use of the two words, based on biological and behavioural differences.